Synthesis, Antimicrobial Evaluation and QSAR Studies of 2-hydroxy Propanoic Acid Derivatives - Bansal, A.; Kumar, P.; Narasimhan, B. (Drug Research, 2014)
A series of 2-hydroxypropanoic acid derivatives (1–26) was synthesized and characterized by physicochemical and spectral means. The synthesized compounds were evaluated for their in vitro antimicrobial potential and the results indicated that compounds 5 and 12 were found to be the most potent antimicrobial agents having pMICam values 1.67 and 1.64 µM/ml respectively. QSAR studies indicated the importance of topological parameter, Kier’s valance second order molecular connectivity index (2χv) in describing the antimicrobial activities of synthesized 2-hydroxypropanoic acid derivatives.
Keywords: antibacterial; antifungal; synthesis; QSAR